Examining argumentation in context fifteen studies on strategic maneuvering - Eemeren, Frans H. van (Argumentation in context, 2009)
Examining Argumentation in Context: Fifteen studies on strategic maneuvering contains a selection of papers on strategic maneuvering in argumentative discourse. Starting point of all of these contributions is that a satisfactory analysis and evaluation of strategic maneuvering is possible only if the argumentative discourse is first situated in the communicative and interactional context in which it occurs. While some of the contributions present general views with regard to strategic maneuvering, other contributions report on the results of empirical studies, examine strategic maneuvering in a particular legal or political context, or highlight the presentational design of strategic maneuvering. Examining Argumentation in Context therefore provides an insightful view of recent developments in the research on strategic maneuvering, which is currently prominent in the study of argumentation.